Odpowiedź :
Odpowiedź:
2x-3+x=8
2x+x=8+3
3x=11//:3
x= 11/3= 3 2/3
b) 3*5x-7=3
15x=3+7
15x=10//15
x=10/15= 2/3
c) 3x-2x+3=1
3x-2x=1-3
x=-2
d) 4x + x/3=4 /*3
12x + x =12
13x=12//13
x=12/13
A) 3x - 3 = 8
3x = 11 | :3
x = 11/3
B) 15x - 7 = 3
15x = 10 |:15
x = 10/15
C) x + 3 = 1
x = -2
zmieniamy znak na przeciwny przy 3 i dlatego jest -2
D) 12x + x = 12
13x = 12 |:13
x = 12/13
prosze o naj
3x = 11 | :3
x = 11/3
B) 15x - 7 = 3
15x = 10 |:15
x = 10/15
C) x + 3 = 1
x = -2
zmieniamy znak na przeciwny przy 3 i dlatego jest -2
D) 12x + x = 12
13x = 12 |:13
x = 12/13
prosze o naj